2010
DOI: 10.1021/ef100479q
|View full text |Cite
|
Sign up to set email alerts
|

Response of Titanium-Isopropoxide-Based Heterogeneous Amphiphilic Polymer Catalysts for Transesterification

Abstract: Transesterification is a widely used reaction in the chemical industry. Currently, industrial-scale transesterification is primarily performed via homogeneous catalysts. Because of downstream separation issues, there is a need for effective heterogeneous catalysts. However, heterogeneous catalysts introduce the drawback of mass-transfer limitations into the reaction system. The substrates associated with transesterification form a three-phase system that is inherently immiscible in each other with liquid/liqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 38 publications
1
20
0
1
Order By: Relevance
“…In 2010, Nawaratna et al reported the first and sole example to date of rationally designed amphiphilic nanoparticles for base-catalyzed reactions. [63] Inspired by a former study on amphiphilic titanium alkoxide oligomers (see Ref. [34] and section 3.1), the authors prepared titaniumisopropoxide-based inorganic dendritic polymers with variable degrees of polymerization ( Figure 13).…”
Section: Amphiphilic Acid/base Catalystsmentioning
confidence: 99%
“…In 2010, Nawaratna et al reported the first and sole example to date of rationally designed amphiphilic nanoparticles for base-catalyzed reactions. [63] Inspired by a former study on amphiphilic titanium alkoxide oligomers (see Ref. [34] and section 3.1), the authors prepared titaniumisopropoxide-based inorganic dendritic polymers with variable degrees of polymerization ( Figure 13).…”
Section: Amphiphilic Acid/base Catalystsmentioning
confidence: 99%
“…This is likely due to the higher amount of triglyceride substrate in the 7:3:2.5 mixture, as in both samples the catalyst concentration is the same. Previous studies with the system (with the only change being the amount of the catalytic surfactant used) resulted in lesser ester yields,13, 14 even after 3 h of reaction time at 200 °C. This observation exemplifies the importance and impact of emulsification ability that a catalyst can bring into systems with immiscible or poorly miscible reactants.…”
Section: Resultsmentioning
confidence: 94%
“…The first stage was adopted to analyze the effect of alkoxide tail group on phase stability of the ternary system while the second stage looked at the alkoxide polymerization effect on the stability of the system. We have discussed the catalytic effects of tail group and polymerization in earlier studies13, 14 and present studies were conducted to ascertain the correlation of phase stability of the ternary system with catalytic effects. In the first stage, titanium ethoxide, titanium propoxide, and titanium butoxide were compared for their effects on the phase stability of the system while in the second stage the effect of titanium isopropoxide was elucidated in more detail.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aus dem Jahr 2010 stammt das erste und bislang einzige Beispiel eines maßgeschneiderten amphiphilen Nanopartikels für basenkatalysierte Reaktionen von Nawaratna et al 63. Inspiriert durch eine frühere Studie zu amphiphilen Titanalkoxidoligomeren (siehe Lit.…”
Section: Katalyse In Durch Amphiphile Katalytische Nanopartikel Stunclassified